Association Between Change in Leisure-Time Physical Activity During the Postretirement Period and Incident Stroke. (19th July 2022) - Li, Xingxing; Liu, Shuangyan; Mu, Xuanwen; Gao, Hui; Zi, Yunhua; Yang, Handong; Zhang, Xiaomin; He, Meian; Yu, Kuai
Abstract : Background and Objectives: To investigate the association of change in leisure-time physical activity (LTPA) occurring during the postretirement period with incident stroke. Methods: The current study enrolled 12, 644 retired workers from the Dongfeng-Tongji cohort from April to October 2013. The change in LTPA was categorized as follows, according to whether the LTPA time met the WHO recommended minimum (at least 150 minutes per week): (1) stayed inactive at both surveys; (2) stayed inactive at the 2008 survey but became active at the 2013 survey; (3) stayed active at the 2008 survey but became inactive at the 2013 survey; (4) stayed active at both surveys. We used multivariable-adjusted Cox proportional hazards regression models to examine the association between change in LTPA and the risk of incident stroke. Results: During 70, 437 person-years of follow-up, we documented 549 incident stroke cases, including 434 incident ischemic stroke cases and 115 incident hemorrhagic stroke (HS) cases. Compared with participants who stayed active at both the 2008 and 2013 surveys, those who were active at the 2008 survey but became inactive at the 2013 survey had significantly higher risks of incident total stroke (hazard ratio [HR] 1.30, 95% CI 1.03, 1.65) and HS (HR 2.34, 95% CI 1.51, 3.63). When stratified by body mass index (BMI) categories, a significant elevated risk of total stroke was seen among overweight participants who stayed active at the 2008 survey but became inactive at the 2013 survey (HR 1.65, 95% CI 1.20, 2.27). The risk of incident stroke decreased with increasing LTPA levels between the 2 surveys (HR of per 150 min/wk increase of LTPA: HR 0.97, 95% CI 0.94, 1.00). In addition, we found that compared with participants who maintained their BMI and stayed active at both the 2008 and 2013 surveys, those who were inactive at both points or who became inactive had higher risks of stroke (HR 2.13, 95% CI 1.09, 4.15; HR 1.50, 95% CI 1.07, 2.08, respectively). Discussion: Among Chinese older adults, increasing LTPA levels during the postretirement period was associated with a lower risk of incident stroke. Retired individuals should be encouraged to participate in LTPA more frequently to lessen future risk of incident stroke.